Child and adolescent well-being and violence prevention in schools - Slee, Phillip T.; Skrzypiec, Grace, 1956-; Cefai, Carmel (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2017)
"This book explores the wide range of ways that educators can understand and promote wellbeing and violence prevention initiatives in schools and communities. Drawing together the two topics of wellbeing and violence prevention and encouraging dialogue between them, the authors address a broad range of contemporary issues including culture, gender and youth voice. Translating theory into practice with a strong evidence-based application, each chapter presents recent research on applications, trends and issues in the field, as well as practical ideas for wellbeing and violence prevention measures"--
Challenges in promoting wellbeing and addressing violence through schools / Shelley Hymel -- Country and wellbeing: Ngarrindjeri speaking as country / Steve Hemming and Daryle Rigney -- Indigenous Australian youth, identity, rap/hip hop: a tool for wellbeing and ethical care / Faye Rosas Blanch -- Measuring subjective wellbeing: findings from Assam wellbeing survey 2013-14 / Udoy Saikai, James Chalmers and Gouranga Dasvarma -- Giving voice: creative practice and a living lab approach / Alison Wotherspoon and Barbara Spears -- Bullying and blooming: addressing the challenges faced by adolescent girls experiencing the early onset of puberty / Donna Swift -- Girls' diminishing wellbeing across the adolescent years / Grace Skrzypiec and Helen Askell-Williams -- Eve-teasing in the guise of school bullying and cyberbullying / Damanjit Sandhu -- Adolescent transgression behaviour: gender differences / Grace Skrzypiec -- Adults' perceptions of bullying in early childhood / Marilyn Campbell and Natalie Morgan -- Early childhood knowledge and understanding of bullying: an approach for early childhood prevention / Lesley-anne Ey and Barbara Spears -- "It's just teasing": responding to conflict in remote Australian schools / John Guenther, Samantha Disbray and Sam Osborne -- The copying of bystanders with cyberbullying in an adolescent population / Georges Steffgen, Andreia P. Costa, and Phillip Slee -- "Surfing the waves": building resilience to promote children's mental health / Carmel Cefai -- Ten ways schools can boost child and adolescent wellbeing when parents separate / Jamie Lee -- Enhancing the wellbeing of young people: the co-creation of a youth mental health space / Kristy Koehne, Allison Hutton, Shane Hough and Christopher Slee -- Stop, connect and collaborate: a school based approach to improve student wellbeing / Nina Mekisic -- Framework for prevention: early interventions to address adolescent violence / Jeanette Stott, Rosalie O'Connor, Trevor Cresswell, Mary McKenna, Robin Swalling, Kay Buckley, Sheila Davidson, and Sally Fordham -- A model for managing student violence / John Maratos -- A program logic framework designed to strengthen the impact and fidelity of wellbeing and behavioural interventions / Ivan Raymond -- Effectiveness of an intervention program for teenage girls with self-harm in Adelaide, South Australia / Mubarak, A.R., Joanna Zeitz and Phillip Slee.
Includes index.
(3eTJQjGJ eYQV GdbGgQI GdOhdj ddcJGH (B2020.s
Keywords: Students -- Mental health; School mental health services; Classroom environment -- Psychological aspects; Well-being.; Bullying in schools -- Prevention; School violence -- Prevention